Effect of Healing Time on Bone-Implant Contact of Orthodontic Micro-Implants: A Histologic Study. (6th April 2014) - Ramazanzadeh, Barat Ali; Fatemi, Kazem; Dehghani, Mahboobe; Mohtasham, Nooshin; Jahanbin, Arezoo; Sadeghian, Hamed
Abstract : Objectives . This study aimed to evaluate the effect of immediate and delayed loading of orthodontic micro-implants on bone-implant contact. Materials and Methods . Sixty four micro-implants were implanted in dog's jaw bone. The micro-implants were divided into loaded and unloaded (control) groups. The control group had two subgroups: four and eight weeks being implanted. The loaded group had two subgroups of immediate loading and delayed (after four weeks healing) loading. Loaded samples were subjected to 200g load for four weeks. After sacrificing the animals micro-implants and surrounding tissues were observed histologically. Bone-implant contact ratios (BIC) were calculated and different groups' results were compared by three-way ANOVA. Results . Mean survival rate was 96.7% in general. Survival rates were 96.7%, 94.4% and 100% for control, immediate and delayed loaded groups, respectively. BIC values were not significantly different in loaded and control groups, immediate and delayed loading groups, and pressure and tension sides. Mandibular micro-implants had significantly higher BIC than maxillary ones in immediate loading, 4-weeks control, and 8-weeks control groups ( P = 0.021, P = 0.009, P = 0.003, resp.). Conclusion Immediate or delayed loading of micro-implants in dog did not cause significant difference in Bone-implant contact which could be concluded that healing time had not significant effect on micro-implant stability.